Becoming Reflective Practitioners: Gender GAP Analysis of Mathematics Student Teachers’ Reflective Practices - Babawande Emmanuel Olawale; Winston Hendricks (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
While reflective thinking practices are thought to be a factor in building bridges between a course of study and personal experience resulting in engaging and personalized learning activities, the present study examined the potential disparities in reflective thinking practices and how they influence preservice mathematics teachers' behavior. Underpinned by a positivist paradigm, the present study employed a quantitative research approach and a survey design. Data was collected from three hundred and fifty-nine mathematics student teachers who were preparing to become mathematics teachers once they had obtained a Bachelor of Education (B.Ed.) degree. Data collected was therefore analyzed through the use of descriptive statistics. Lifelong learning skills, self-assessment, self-belief, teaching awareness, and reflective thinking were all examined using a framework based on five components. Research findings revealed that while reflective thinking practices are often emphasized in teacher education programs, results clearly show that the process of reflective practices is conceptualized differently by female and male participants. Research findings also revealed that constructs such as lifelong learning skills, self-assessment ability, and teaching awareness have a more decisive influence on male participants than their female counterparts. This resulted in male participants having less perception of the usefulness of reflective thinking practices. Based on the findings, it was suggested that various support systems should be developed in mathematics teacher education programs to facilitate more independent and self-directed reflective thinking practices among both female and male mathematics students teachers. Keywords: Classroom Practices, Gender GAP, Reflective Thinking, Self-Belief, Teacher Education.